Climate Change and Food Security in Dryland Region of the World - Chhetri, Netra B; Easterling, Willam E (Annals of Arid Zone, 2016)
Some of the most profound and direct impacts of climate change over the next few decades will be on systems of food production. The sensitivity of crop production to climate makes agriculture vulnerable to the risks associated with climate change. While it is generally acknowledged that climate change may not imperil the ability of world’s agriculture to maintain food security, it does, however, challenge farmers to adapt in regions where it may be stressful, such as dry land areas of the world. World’s dryland farmers with limited capacities to adapt to climate variability and change are faced with the new threats, which could have serious impacts on food security. The vulnerability of agriculture to climate change in dry land regions of the world also comes from factors associated with socioeconomic, political, and technological conditions limiting their ability to adapt to change. However, adaptations to climate change could reduce the impact considerably. Key words: Climate change, dryland agriculture. food security, impacts and adaptation.